A 16-week school-based intervention improves physical fitness in Slovenian children: a randomized controlled trial - Petrušič, Tanja; Novak, Dario (Frontiers in Physiology, 2024)
Introduction: The aim of this study was to evaluate the effects of a 16-week school-based physical activity (PA) intervention on physical fitness (PF) (speed, hand-eye coordination, flexibility) of 8– to 9-year-olds. Methods: A total of seventy-eight boys and girls (boys: n = 45, aged 8.4 ± 4.9 years; girls: n = 42, aged 8.6 ± 0.5 years) from a school in Slovenia were randomly assigned to either a group with an after-school PA program (EXP) or a control group (CON) that participated exclusively in mandatory physical education (PE). The EXP group engaged in the extracurricular PA program for 60 min twice a week for 16 weeks, concurrent with regular PE classes. The program primarily involved elementary PE games that included elements of athletics (e.g., skipping, push- off running, hopping, crossstepping, and jumping) and gymnastics (e.g., handstand, forward roll, backward roll, hand support jumps, squat jump on a vault box, climbing on horizontal bars, incline benches and ropes, crawling, and jumping rope). Standardized tests appropriate for this age group were used to assess PF, including the sit and reach test (SAR), the 30-meter sprint, and the alternate hand wall toss test at distances of 1.0 and 2.0 m (AHWT 1.0 and 2.0). Results: There was a significant group-time interaction for SAR test (EXP group increase: +1.6 cm, +6.3%; CON group decrease: −0.1 cm, −0.4%; p < 0.001, ηp2 = 0.361), and the 30 m sprint (EXP group improvement: −0.4 s, −6.3%; CON group decrease: +0.1 s, +1.6%; p < 0.001, ηp2 = 0.193). Similarly, the EXP group improved by +2.1 points (+25.6%) in the 1.0 m wall throw with the alternating hand, while the CON group showed only minimal changes (−0.2 points, −2.4%; p < 0.001, ηp2 = 0.545). No significant interaction was found for the 2.0 m toss (EXP and CON group both −0.1 points, −2.6%; p = 0.888, ηp2 = 0.001). Post-hoc analyses with paired t-tests revealed that the EXP group showed significant improvements in SAR test (p < 0.001), 30 m sprint (p < 0.001) and AHWT 1.0 test (p < 0.001), while the CON group showed no significant changes in SAR test (p = 0.533), 30 m sprint (p = 0.150), AHWT 1.0 test (p = 0.186) and AHWT 2.0 test (p = 0.430). Discussion: The results of the study showed that the extracurricular program with only two additional weekly sessions significantly improved the components of PF in 8- to 9-year olds. Significant improvements were observed in the areas of flexibility, speed and coordination, as shown in the SAR test, 30-meter sprint and 1.0-meter handwall toss tests. However, no similar improvements were observed in the 2.0-meter handwall toss, which illustrates the specific areas of impact of the program.